Effects of Vertical Direction and Aperture Size on the Perception of Visual Acceleration. (June 2016) - Mueller, Alexandra S.; González, Esther G.; McNorgan, Chris; Steinbach, Martin J.; Timney, Brian
It is not well understood whether the distance over which moving stimuli are visible affects our sensitivity to the presence of acceleration or our ability to track such stimuli. It is also uncertain whether our experience with gravity creates anisotropies in how we detect vertical acceleration and deceleration. To address these questions, we varied the vertical extent of the aperture through which we presented vertically accelerating and decelerating random dot arrays. We hypothesized that observers would better detect and pursue accelerating and decelerating stimuli that extend over larger than smaller distances. In Experiment 1, we tested the effects of vertical direction and aperture size on acceleration and deceleration detection accuracy. Results indicated that detection is better for downward motion and for large apertures, but there is no difference between vertical acceleration and deceleration detection. A control experiment revealed that our manipulation of vertical aperture size affects the ability to track vertical motion. Smooth pursuit is better (i.e., with higher peak velocities) for large apertures than for small apertures. Our findings suggest that the ability to detect vertical acceleration and deceleration varies as a function of the direction and vertical extent over which an observer can track the moving stimulus.